Alteration of Platelet Aggregation by Cigarette Smoke and Carbon Monoxide - Mansouri, Ali; Perry, Carol A (Thrombosis and Haemostasis, 1982)
Platelet aggregation with epinephrine, adenosine diphosphate and arachidonic acid was studied in the presence of cigarette smoke and carbon monoxide. It is shown that cigarette smoke inhibits the arachidonic acid induced platelet aggregation as well as the second phase of epinephrine induced aggregation. The adenosine diphosphate induced platelet aggregation is not significantly affected by cigarette smoke. Carbon monoxide causes similar alterations in platelet aggregation. These results suggest that cigarette smoke inhibits platelet aggregation. This aggregation inhibition is due to the presence of carbon monoxide.
Keywords: Adenosine diphosphate (ADP); Carbon monoxide (CO); Platelet rich plasma (PRP); Platelet poor plasma (PPP)